Proximal versus Distal Recipient Vessels in Lower Extremity Reconstruction: A Retrospective Series and Systematic Review - Stranix, John T.; Borab, Zachary M.; Rifkin, William J.; Jacoby, Adam; Lee, Z-Hye; Anzai, Lavinia; Ceradini, Daniel J.; Thanik, Vishal; Saadeh, Pierre B.; Levine, Jamie P. (Journal of Reconstructive Microsurgery, 2018)
Background Recipient vessels proximal to the zone of injury have traditionally been preferred for lower extremity reconstruction. However, more recent data have shown mixed outcomes when performing anastomoses distal to the zone of injury. We investigated the impact of recipient vessel location on free flap outcomes.Methods Retrospective review (1979–2016); 312 soft tissue free flaps for open tibia fractures met inclusion criteria. Flap characteristics and perioperative outcomes were examined. Systematic review identified articles evaluating anastomosis location and flap outcomes; pooled data analysis was performed.Results More anastomoses were performed proximal to the zone of injury (80.7%) than distal (19.3%). Distal anastomoses were not associated with increased take back rates (19.6%) compared with proximal (23.8%) anastomoses (p = 0.356). Regression analysis comparing proximal and distal anastomoses found no difference in partial flap failures (7.4% vs 11.9%; p = 0.978) or total flap failures (9.3% vs 9.3%; p = 0.815) when controlling for the presence of arterial injury, flap type, and time from injury to coverage. Systematic review yielded 11 articles with 1,245 proximal and 127 distal anastomoses for comparison. Pooled analysis (p = 0.58) and weighted comparative analysis (p = 0.39) found no difference in flap failure rates between proximal and distal groups.Conclusion Our results are congruent with the current lower extremity literature and demonstrate no difference in perioperative complication rates between anastomoses performed proximal or distal to the zone of injury. These findings suggest that anastomotic location choice should be based primarily on recipient vessel quality/flow and ease of access/exposure rather than orientation relative to the zone of injury.
Keywords: lower extremity reconstruction; zone of injury; recipient vessels